2021
DOI: 10.1515/jom-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic manipulative medicine in the management of headaches associated with postconcussion syndrome

Abstract: Context Previous studies have demonstrated the effectiveness of osteopathic manipulative treatment (OMT) for various headache types, with limited evidence of its use for headaches related to mild traumatic brain injury (MTBI). No studies prior studies were found regarding OMT for headaches in patients with postconcussion syndrome (PCS), defined as symptom persistence for longer than 3 months after MTBI. Objectives To evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Treatment was associated with a significant reduction of pain index 2 weeks after the end of treatment, but this effect was no more statistically significant 5 weeks later [ 50 ]. Esterov et al (2021) [ 51 ] showed a reduction in pain in 26 participants assessed using a visual analogic scale after an osteopathic manipulative treatment, but no significant difference regarding pain was found within the questionnaire results.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment was associated with a significant reduction of pain index 2 weeks after the end of treatment, but this effect was no more statistically significant 5 weeks later [ 50 ]. Esterov et al (2021) [ 51 ] showed a reduction in pain in 26 participants assessed using a visual analogic scale after an osteopathic manipulative treatment, but no significant difference regarding pain was found within the questionnaire results.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent reviews [ 75 , 76 , 77 ] focused on the effect of physical exercise in patients with persistent PCS and found that exercise significantly reduced the severity of PCS, the percentage of patients with PCS, and days off work, as compared to controls. Other recent reviews addressed issues such as interventions in sport-related concussion [ 17 , 78 ], reporting evidence in support of cervical rehabilitation, vestibulo-ocular rehabilitation, aerobic exercise, or rTMS [ 51 , 79 ], suggesting promising preliminary results for the treatment of post-concussive depression and headaches. As previously mentioned, a systematic review with meta-analysis provided only very low to low levels of evidence to support commonly applied non-pharmacological interventions for persistent PCS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations